Kegiatan Penghijauan Penanaman 150 Bibit Pohon di Desa Wonorejo Kecamatan Kaliwungu Kabupaten Kendal - Solikhatun Fitri; Fatih Abdan Syakuuro (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Trees play an important role in carbon sequestration and the global carbon cycle, contributing to climate change mitigation. The carbon dioxide cycle maintains a natural balance between concentrations in the atmosphere. The government mandate along with the Minister of Environment and Forestry's directive is to plant 200 trees in a lifetime. Trees are one way to reduce pollution, there is very little activity along the main roads of the village so this had to be done. The purpose of this work is to create a beautiful environment on the main road of the village so that the activities and benefits can be heard by the community. In this process the trees planted were Ketapang Kenka, Sengon, Glodogan and Pachira trees. Fruit trees can not only be utilized for air conditioning and disaster prevention, the community can also manage fruit trees. The community can see from the work that has been done that the community really appreciates the work. This can be seen from the enthusiasm of the community and village owners who participated in the tree planting activity.